Development and Maintenance Mechanisms of a Long-Lived Mesoscale Vortex Which Governed the Earlier Stage of the “21.7” Henan Torrential Rainfall Event - Li, Wanli; Ma, Hui; Fu, Rui; Han, Hong; Wang, Xiuming (Frontiers in Earth Science, 2022)
From 17 to 22 July 2021, a series of disastrous rainstorms appeared within Henan Province and its surroundings, which rendered 398 dead/missing and a direct economic loss of up to ~114 billion Yuan. This event was named as the “21.7” Henan torrential rainfall event (TRE), and it could be divided roughly into three stages according to the precipitation features and dominant weather systems. This study mainly focused on the development and maintenance mechanisms of a long-lived (72 h) quasi-stationary mesoscale vortex that governed the earlier stage of the “21.7” TRE. Main results are as follows: (i) the mesoscale vortex formed/maintained in a favorable environment which was characterized by the South-Asia-high associated divergence in the upper troposphere, and the relay transport of relatively cold air by the trough and high-pressure system in the middle troposphere. (ii) the vertical stretching due to lower-level convergence and the upward transport of cyclonic vorticity by ascending motions served as the first and second dominant factors for the mesoscale vortex’s rapid development and long-time maintenance, whereas, the import/export transport of anticyclonic/cyclonic vorticity into/from the vortex’s central region and the tilting effects were mainly detrimental for the vortex’s development/maintenance. (iii) the air particles that formed the mesoscale vortex mainly came from the levels below 1500 m, within the regions in lower latitudes. The air particles experienced notable precipitation before the formation of the mesoscale vortex, which contributed to the vortex’s formation through latent heat release.